Ghoib Divorce Lawsuit in The Perspective of Islamic Law: Analysis of Ghoib's Divorce Lawsuit in 2024 at the Purworejo Religious Court Class 1B - Hari Widiyanto; Nila Fadlilatul Husna; Alifia Nadia Salsabila; Muhajir Muhajir (CV. ULIL ALBAB CORP, 2025)
The main focus of the research is the phenomenon of supernatural divorce, which is a legal remedy for the wife to end the marriage when her husband's whereabouts are unknown. The research uses a qualitative method with a phenomenological approach to explore the mechanism, causal factors, and impact of supernatural divorce. Primary data was collected through in-depth interviews with informants, while secondary data was obtained from related agency documents, books, and journals. The results of the study show that supernatural divorce lawsuits are regulated in Law Number 7 of 1989, the Compilation of Islamic Law, and other regulations. The court process includes summoning the defendant through the mass media and a verstek decision if the defendant is not present. In 2024, there will be 99 cases of supernatural divorce lawsuits at the Purworejo Religious Court, reflecting the high divorce rate. The analysis method includes data reduction, data presentation, and conclusion drawn. This research highlights the importance of legal protection for wives and the role of the court in ensuring justice for related parties.